The Influence of Digital Financial Inclusion, Access to Finance, and Financial Management on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) in the Retail Sector in Bandar Lampung City - Septi Wahyuni; Lestari Wuryanti; Muhammad Irfan Pratama (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the influence of digital financial inclusion, access to financing, and financial management on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the trade (retail) sector in Bandar Lampung City. MSMEs have a strategic role in the economy, but still face various challenges, especially in the use of digital financial technology, limited access to formal financing, and low systematic financial management practices. This research uses a quantitative approach with descriptive and verifiable methods. Data was collected through the distribution of questionnaires to retail MSME actors in Bandar Lampung using purposive sampling techniques. Data analysis was carried out using validity tests, reliability tests, classical assumption tests, and multiple linear regressions with t-test, F test, and determination coefficient (R²). The results of the study show that digital financial inclusion, access to financing, and financial management have a positive and significant effect on the financial performance of MSMEs, respectively. Simultaneously, these three variables also have a significant effect on the financial performance of retail MSMEs in Bandar Lampung City. These findings emphasize the importance of increasing digital financial literacy, easy access to financing, and implementing good financial management to improve the sustainability and competitiveness of MSMEs.